Adaptability and Stability of Soybean Cultivars in Lowland Production System - Scapini Balest, Darlan; Bisognin, Dílson Antônio; Uhry Junior, Darci Francisco; Gerzson Badinelli, Pablo; Gaklik Waldow, Daniel Arthur; Junior Zanon, Alencar (Revista Ceres, 2022)
The objective was to study the adaptability and stability of soybean cultivars in the lowland production system under different conditions in a subtropical environment. Fourteen soybean cultivars were evaluated in five locations and three growing seasons in Rio Grande do Sul State, Brazil. Three sowing dates were evaluated in each location and growing season and named as: early, recommended for high yield and recommended to minimize the risk of water deficiency. The experiment was carried out in a randomized complete block design, with three replicates. Yield data was submitted to analysis of variance, and the Eberhart and Russel method was used to study its adaptability and stability. In general, the cultivars that showed adaptability and stability to the three sowing dates showed MG between 5.6 to 6.4 and the type of indeterminate growth. The cultivars A 6411 RG, TEC 5936 IPRO and TECIRGA 6070 RR combined wide adaptability and stability, the cultivars Fundacep 65 RR and 6869 RSF RR presented high yield and stability of production and are recommended for lowland environments.